Treating multiple sclerosis with monoclonal antibodies: a 2013 update. (March 2013) - Deiß, Annika; Brecht, Isabel; Haarmann, Axel; Buttmann, Mathias
The third part of this in-depth review series on the treatment of multiple sclerosis (MS) with monoclonal antibodies covers the years 2010–2012. The natalizumab section gives a progressive multifocal leukoencephalopathy update, focusing on clinically relevant aspects. Furthermore, it outlines problems around natalizumab cessation and current evidence on therapeutic strategies thereafter. Finally, it reviews evidence on Janus-faced modes of natalizumab action besides anti-inflammatory effects, including proinflammatory effects. The section on alemtuzumab critically analyzes recent Phase III results and discusses which patients might be best suited for alemtuzumab treatment, and reviews the long-term immunological impact of this anti-CD52 antibody. The daclizumab section critically summarizes results from the Phase IIb SELECT/SELECTION trial and introduces the Phase III program. The section on anti-CD20 antibodies reviews Phase II results on ocrelizumab and ofatumumab, and discusses current perspectives of these antibodies for MS therapy. Promising recent Phase II results on the anti-IL-17A antibody secukinumab (AIN457) are outlined and a short update on tabalumab (LY2127399) is given. Other highlighted antibodies currently being tested in MS patients include GNbAC1, BIIB033, MOR103 and MEDI-551. Finally, the authors give an update on the role monoclonal antibodies could play in the therapeutic armamentarium for MS in the medium term.